Exploring the efficacy and mechanism of Qingxuan decoction in treating opioid-induced constipation - Yarong Zhang; Haoshi Cao; Linling Su; Xianxia Yuan; Ling Mo; Wenyu Jiang; Xiaoli Feng; Dongling Liu; Yang Hai (Pharmacological Research - Modern Chinese Medicine)
Objective: This study aimed to investigate the formulation of Qing Xuan Decoction (QXD) and its possible mechanism of action in the treatment of opioid-induced constipation (OIC). Methods: We used orthogonal design experiments to optimize the decoction and ethanol precipitation process for QXD. The efficacy of QXD on loperamide - induced constipation in mice was explored via intestinal motility assay and defecation study. We examined the influence of QXD on the intestinal microbiota of mice through 16S rRNA sequencing. We assessed the alterations in the H2O2 and superoxide anion scavenging rates in serum using commercial kits. Results: The optimal decoction protocol for QXD entails boiling it with a 10 - fold volume of water for three consecutive cycles, each lasting 1.5 h. The optimized ethanol precipitation process requires using 85 % ethanol and performing the procedure three times, with each instance of precipitation lasting over 48 h. QXD enhanced small intestine propulsion rate and defecation efficacy, significantly ameliorating loperamide-induced constipation. QXD increased the abundance of Bacteroides, Prevotella, and Akkermansia in the intestine, decreased the abundance of Desulfovibrio, and kept the intestinal flora balanced. QXD mitigated oxidative stress by decreasing H₂O₂ levels and augmenting superoxide anion scavenging ability. Conclusion: QXD is expected to be a promising therapeutic drug for OIC, and its mechanism of action may be to alleviate constipation by regulating the homeostasis of intestinal flora while reducing oxidative stress.